PERAN CUSTOMER SERVICE DALAM MEMBANGUN LOYALITAS PELANGGAN DI PT FEDERAL INTERNASIONAL - Amanda Anjili; Maya Richmayati; Elminaliya Sandra (PUAN INDONESIA, 2026)
The competitive competition requires companies to create new ideas from the service which is given to the consumers in order to maintain their consumers for not switching to other competitors. Nowadays, there are companies focus on leasing, factoring, and consumer finance. This study aims to test the impact of the quality service towards the consumer's loyalty through the consumer's satisfaction in Federal International Finance. The type of this study is a quantitative research. The population of this study are all the customers of the Federal International Finance, with 96 customers as the samples and this study applies the probability sampling with the simple random sampling method. The data analysis applies the path analysis with Smart PLS 3.0 program. The result of this study shows that the service quality impacts the customer's satisfaction. The service quality and the customer's satisfaction impact the customer's loyalty. The service quality impacts the impacts the customer's loyalty through the customer's satisfaction. Therefore, it can be concluded that the customers satisfaction mediate the service quality to the consumers loyalty